(untitled) (Dhaka University Law Journal, 2026)
This paper reflects on the remedial aspects of constitutional conventions. It discerns three varying approaches from the jurisprudence of courts of different jurisdictions, mainly of Bangladesh, India, the UK, and Canada: judicial enforcement; judicial declaration; and extra-judicial relief. In Idrisur Rahman, the Supreme Court of Bangladesh enforced the President’s conventional consultation with the Chief Justice in the matter of appointment of Judges of the Supreme Court. This paper argues that the Court should have judged the two other forms of remedies still followed notably in the English jurisdiction, the mother country of constitutional conventions. The Court did not justify why it preferred to judicially enforce conventions when in the UK and Canada, violation of conventions is still left to the political verdict, or, if Courts involve themselves at all, they limit themselves to only declaring the existence of the convention but not enforcing it. Idrisur Rahamn is clearly deficient since it omitted an analysis of the comparative merits and demerits of different approaches to the violation of conventions. But this is an essential aspect of analysis if a Court decides to enforce conventions. These omissions, to this author’s view, have rendered Idrisur Rahman a weak authority on the subject. This paper is to provide for the said omissions of Idrisur Rahman. The attempt may guide the Supreme Court in any future litigation dealing with conventions in general or the issue of an appropriate remedy for the violation of conventions. Dhaka University Law Journal, 2025, 36(2), 113-140